2014
DOI: 10.1215/00127094-2410289
|View full text |Cite
|
Sign up to set email alerts
|

Tropical combinatorics and Whittaker functions

Abstract: We establish a fundamental connection between the geometric RSK correspondence and GL(N, R)-Whittaker functions, analogous to the well known relationship between the RSK correspondence and Schur functions. This gives rise to a natural family of measures associated with GL(N, R)-Whittaker functions which are the analogues in this setting of the Schur measures on integer partitions. The corresponding analogue of the Cauchy-Littlewood identity can be seen as a generalisation of an integral identity for GL(N, R)-W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
263
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 136 publications
(274 citation statements)
references
References 57 publications
10
263
0
1
Order By: Relevance
“…(Subsequent to this paper, a generalization of this model called the Beta Polymer was discovered and analyzed in [2]). The strict-weak model introduced here differs from the earlier studied log-gamma polymer [9,10,15] in the definition of the admissible polymer paths. The strict-weak model uses gamma-distributed weights on the edges (or vertices, depending on the formulation chosen) while the log-gamma polymer uses inverse gamma weights.…”
Section: Introduction and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Subsequent to this paper, a generalization of this model called the Beta Polymer was discovered and analyzed in [2]). The strict-weak model introduced here differs from the earlier studied log-gamma polymer [9,10,15] in the definition of the admissible polymer paths. The strict-weak model uses gamma-distributed weights on the edges (or vertices, depending on the formulation chosen) while the log-gamma polymer uses inverse gamma weights.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…As explained in [14], the analog of the smallest part for the pure alpha Whittaker process is related to the strict-weak polymer free energy. Methods coming from Whittaker processes [10] provide a route to write down a Laplace transform formula for the strict-weak polymer partition function which can be turned (using identities similar to those of [9]) into the Fredholm determinant formula present herein. This is the approach taken in [14].…”
Section: Theorem 13mentioning
confidence: 99%
“…Using A.N. Kirillov's [71,85] tropical RSK correspondence, Corwin, O'Connell, Seppäläinen and Zygouras [39] introduce a different Whittaker process to describe the free energy hierarchy for this polymer (see Section 5.3 for more on this). Presently we call this the α-Whittaker process (see Section 4.2) and it arises as the limit of the Macdonald process when ρ is a pure alpha specialization (some α i > 0, β i = 0 for all i ≥ 1 and γ = 0).…”
Section: Tracy-widom Asymptotics For Polymer Free Energymentioning
confidence: 99%
“…Analogously to the O'Connell-Yor semi-discrete polymer, the hierarchy f (n) evolves as a Markov chain in n with state space in R N (N +1)/2 . An explicit construction of this Markov chain as a function of the weights d is given in [39] (appealing to the recursive formulation of the tropical RSK correspondence which is given in [85]). We will not restate the kernel of this Markov chain on R N (N +1)/2 , but only remark that it is not the same as the limiting Markov chain which corresponds to the scaling limit of the dynamics given in Proposition 2.3.5.…”
Section: Log-gamma Discrete Directed Polymermentioning
confidence: 99%
“…Versions of this conjecture have been proved for two related models in the point-to-point case: the continuum random polymer in [ACQ11] (building on results of [TW08a; TW08b; TW09]) and the semi-discrete polymer of O'Connell and Yor in [BC11; BCF12] (see also [O'C12]). In the setting of discrete directed random polymers, [COSZ11] showed that if the weights are chosen so that −w i,j is distributed as the logarithm of a Gamma random variable with parameter θ i +θ j (for some fixed θ i 's andθ j 's) then the model is exactly solvable in the sense explained above. This was later used in [BCR13] to prove that the asymptotic fluctuations of the free energy of the point-to-point polymer (at least for low enough temperature) have the conjectured Tracy-Widom GUE distribution.…”
Section: Tracy-widom Distributionsmentioning
confidence: 99%